The silver chair - Thwaites, David; Power, Camilla, 1976-; Baker, Tom, 1934-; Kirby, Alex.; Seymour, Alan, 1927-; Lewis, C. S. (Clive Staples), 1898-1963.; British Broadcasting Corporation. Television Service; WonderWorks, Ltd. ([Chicago] : Home Vision Entertainment, 2002)
Eustace is summoned back to the magical land of Narnia with his new friend Jill. Many years have passed since Eustace's last visit. King Caspian is old and frail. The mysterious disappearance years ago of his son, Prince Rilian, has remained unsolved. Aslan the lion charges the children to embark on a perilous journey through enchanted lands of giants and witches to find Rilian and bring him home.
Based on the story of the same title by C.S. Lewis.
Originally broadcast by the BBC in 1990.
Special features: interactive trivia game for kids ; stills gallery.
David Thwaites, Camilla Power, Tom Baker.
DVD.
Closed-captioned.
Keywords: Narnia (Imaginary place) -- Drama; Narnia (Imaginary place) -- Juvenile drama; Fantasy television programs -- Great Britain; Children's television programs